Bakti pada Tuhan dalam Tri Hita Karana - Kartika, Ni Gusti Ayu (Widya Duta: Jurnal Ilmiah Ilmu Agama dan Ilmu Sosial Budaya, 2020)
The essence of religion is trust and devotion to God Almighty. Therefore, one of the most important elements of Tri Hita Karana is building a harmonious relationship with God by way of trust and devotion. In order to be devoted to God it can be effective for this life should believe and devotion to God as the main characteristic of religious life. There are three ways to serve God, namely: Swa Artha, Para Artha and Parama Artha.In the concept of Hindu community life, Tri Hita Karana is the concept of balance, harmony and harmony between the great bhuana and alit bhuana whose axis lies in human service before Ida Hyang Parama Kawi. The implementation of the Tri Hita Karana concept in question is emphasized that all three elements must be applied in a whole and integrated manner. None of the Parahyangan, Pawongan, and Palemahan elements occupy a special portion. All elements are always balanced in thought, balanced in speech and also balanced in all actions. There are nine ways of devoting to God from implementation, namely: Åšravaá¹‡am, KÄ«rtanam, Smaraá¹‡am, Arcaá¹‡am, Wandanam, Dasyanam, Padasewanam, Sakhyanam, á¾¹tmaniwedanam.